Tingkat Pengetahuan Masyarakat tentang Penggunaan Antibiotik yang Rasional di Kelurahan Rantepao, Kecamatan Rantepao, Kabupaten Toraja Utara - Ary Kristanto Lallo; Yasavati Kurnia Nah; Theresia Citraningtyas (Jurnal MedScientiae, 2023)
Antibiotics are medicine used to overcome bacterial infections. Proper use of antibiotics is very important to note because the side effects caused are quite dangerous and improper use of antibiotics can cause antibiotic resistance. This research was conducted to find out how much the level of public knowledge in Malango Sub-district about the rational use of antibiotics. This research is descriptive research with sampling techniques used convenience sampling as many as 100 respondents with questionnaires as the research tool. The data analysis used is univariate measured in the SPSS program. The results of the study found that the level of public knowledge in Malango Sub-disctrict in the use of rational antibiotics arranged by 10% of excellent comprehension. 52% of passable comprehension and 38% of less comprehension. In conclusion, public knowledge in Malango Sub-district tends to enough comprehension.